2018
DOI: 10.1002/adsc.201801116
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Al‐Catalysed TandemC−N/C−SeBond Formation of Isoselenocyanates with Aziridines: Synthesis and DFT Study

Abstract: Al-catalyzed stereospecific tandem CÀN/ CÀSe bond formation of chiral aziridines with isoselenocyanates is described with 90-99% ee and 77-91% yields. The mechanistic investigation using the computational study suggests that the reaction involves a concerted pathway (S N 2). The selectivity and substrate scope are the important practical features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In the same year, Punniyamurthy and Cowokers described a way to make pentane (R)‐2‐iminoselenazolidine 87 with selenium from isoselenocyanates 85 and chiral aziridines 86 (Scheme 19). [37] Their method worked 90–99 % of the time and had a yield of 77–91 %. It is thought that combining isoselenocyanate 85 with Al‐salen could make Al‐complex I .…”
Section: Synthesis Of Chiral Organoselenium Compoundsmentioning
confidence: 99%
“…In the same year, Punniyamurthy and Cowokers described a way to make pentane (R)‐2‐iminoselenazolidine 87 with selenium from isoselenocyanates 85 and chiral aziridines 86 (Scheme 19). [37] Their method worked 90–99 % of the time and had a yield of 77–91 %. It is thought that combining isoselenocyanate 85 with Al‐salen could make Al‐complex I .…”
Section: Synthesis Of Chiral Organoselenium Compoundsmentioning
confidence: 99%
“…A similar process employing thiols and selenols as nucleophiles was reported by Wosińska-Hrydczuk and Skarżewski. [96] Punniyamurthy et al [105] employed various chiral metal-salen catalysts such as 148 to promote a ringopening/recyclization sequence of chiral aziridines 147 that inverted the configuration of the existing stereocenter. Computational studies indicated that the process was concerted (Scheme 30).…”
Section: Asymmetric Reactions Of Selenium Nucleophilesmentioning
confidence: 99%